THE TECHNOLOGY OF USING INTERACTIVE AND PROBLEM-BASED RESEARCH METHODS IN TEACHING HUMAN ANATOMY AND PHYSIOLOGY - Xamidova Dilbar Giyosovna (International Scientific and Current Research Conferences, 2024)
This article provides information about the technology of using interactive and problem-based teaching methods in human anatomy and physiology lessons. Keywords: interactive, problem-based research methods Subject-object, role-playing games, conference, court lessons, brainstorming, cluster method.